1990
DOI: 10.1016/s0022-5347(17)40071-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and Crystal Adherence to the Surfaces of Indwelling Urethral Catheters

Abstract: Bacterial and crystal adherence to the surfaces of indwelling urethral catheters was investigated by scanning electron microscopy and immunofluorescence method in relation to microbiological examination. Gram-negative bacteria were isolated more frequently than gram-positive bacteria in urine and catheter cultures. Microorganisms and crystals frequently were associated with fibrillar material, some of which was considered to be fibrin. On the surfaces of catheters indwelling for more than 1 week bacteria often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…26 Several such adhesins have been identified on P. mirabilis cells 18 and protein coatings have been found on catheters removed from patients after short periods. 27 Although P. mirabilis can probably attach to conditioning films, in this way they can also bind directly to silicone surfaces. 28 Powerful physical forces can also initiate crystalline biofilm formation.…”
Section: Mechanisms Of Crystalline Biofilm Formationmentioning
confidence: 99%
“…26 Several such adhesins have been identified on P. mirabilis cells 18 and protein coatings have been found on catheters removed from patients after short periods. 27 Although P. mirabilis can probably attach to conditioning films, in this way they can also bind directly to silicone surfaces. 28 Powerful physical forces can also initiate crystalline biofilm formation.…”
Section: Mechanisms Of Crystalline Biofilm Formationmentioning
confidence: 99%
“…The incidence of infection in patients with indwelling catheters increases 5 to 10% per day (4,41). Within 3 weeks of use, 100% of patients with indwelling catheters will acquire UTIs due to the establishment of biofilms on the catheter material (4,24). Scanning electron microscopy has shown that most catheters removed from patients after only 7 days are colonized by bacterial biofilms (4).…”
mentioning
confidence: 99%
“…Scanning electron microscopy has shown that most catheters removed from patients after only 7 days are colonized by bacterial biofilms (4). Biofilms persist in the urinary tract and on catheter surfaces because the microorganisms contained within a biofilm are well protected from urine flow and host defense mechanisms (19,24). More importantly, bacteria within biofilms are strongly resistant to antibiotic therapy (11)(12)(13)17).…”
mentioning
confidence: 99%
“…According to Ganderton et al, (1992), biofilms containing 5 x 10 9 viable cells per centimeter can be found on long-term indwelling catheters removed from patients. Ohkawa et al, (1990) for example, found that 21 of 28 catheters removed after 7 to 16 days were colonized by biofilm. These biofilms can form on the outer surface of the catheter around the balloon and catheter tip, and can cause trauma to the bladder and urethral epithelia.…”
Section: Discussionmentioning
confidence: 99%